1999
DOI: 10.1111/j.1945-1474.1999.tb00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Cultural Values, Beliefs, and Practices and Patient Falls: A Middle Eastern Study

Abstract: Patient falls have been a concern in North American healthcare for many years. Studies have examined environmental, clinical, and patient variables for purposes of risk identification and fall reduction, primarily in the context of Western societies. An investigation at King Faisal Specialist Hospital and Research Centre in Riyadh, Saudi Arabia, began in 1993 to determine whether commonly reported risk factors apply to the Saudi patient population and whether cultural values, beliefs, and practices such as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It is reported that adequately designed and built ablution spaces in mosques are rarely found (Omer, 2014; Ebrahimi and Yusoff, 2018). Improperly designed ablution areas are not only inadequate for use but also initiate risks since discernible amounts of waters and/or pollutants (mainly soapsuds) are frequently scattered on ablution floors from worshippers’ washing practices (Hilliard et al , 1999; Mokhtar, 2003). As a result, ablution floors are often slippery which may directly lead to the falling of people performing their ablution.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that adequately designed and built ablution spaces in mosques are rarely found (Omer, 2014; Ebrahimi and Yusoff, 2018). Improperly designed ablution areas are not only inadequate for use but also initiate risks since discernible amounts of waters and/or pollutants (mainly soapsuds) are frequently scattered on ablution floors from worshippers’ washing practices (Hilliard et al , 1999; Mokhtar, 2003). As a result, ablution floors are often slippery which may directly lead to the falling of people performing their ablution.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature stated that adequately designed and built ablution spaces in mosques are rarely found (Omer, 2014; Ebrahimi and Yusoff, 2018). Inadequately designed ablution areas are not only insufficient for use but also introduce dangers since perceptible amounts of water and/or pollutants (soapsuds) are often dispersed on ablution floors from prayers’ washing practices (Hilliard et al , 1999; Mokhtar, 2003). As a result, ablution floors can be turned into slick conditions.…”
Section: Introductionmentioning
confidence: 99%